Call to action: Clinical pharmacist roles and opportunities in health disparities research. Issue 3 (8th February 2023) - Marrs, Joel C.; Formea, Christine M.; Abdalla, Maha; Brual, Rochelle L.; Crowe, Susie J.; Freibert, Kirstie H.; Herink, Megan C.; Hoffman, Alexander R.; Philbrick, Ann M.; Prescott, Gina M.; Shahdoost Moghadam, Sara; Zhou, Crystal
Abstract: The roles clinical pharmacists can play in addressing health equity and eliminating health disparities span the areas of quality of care, access to care, use of care, and health outcomes. Through this call to action, we address the importance of dismantling health disparities and describe the potential barriers and challenges to clinical pharmacists becoming involved with and performing health disparities research. Furthermore, we identify solutions to these barriers and challenges by highlighting opportunities for clinical pharmacists to seek training and identify potential funding sources for health disparities research. In addition, we provide examples of previous health disparities research conducted by pharmacists across a wide spectrum of patient populations, areas of practice, and types of research. The goal moving forward is to continue to promote current training opportunities to allow clinical pharmacists to develop and/or improve on their research skillset to expand pharmacist‐led research within the focus area of health disparities and ultimately serve as leaders and collaborators in the area.